Use of digital technologies in education of agricultural students - Buribayeva Gulchehra Norkuziyevna (Peerian Journals Publishing, 2024)
Resolution PQ-216 dated 07.07.2023 "On additional measures to increase quality and efficiency by integrating science, education and production in the agricultural sector" was signed by the President of the Republic of Uzbekistan. From September 1 of this year, cooperation with higher education and research institutions, the introduction of innovative technologies, and the development of human resources are one of the license and permit procedures for the establishment of newly established agricultures, cooperatives, and other large enterprises in the field.
Keywords: newly; license; procedures; establishment